Analisis Manajemen Risiko Berdasarkan ISO 31000: 2018 pada UMKM Spark Design dalam Operasional Jasa Desain Grafis - Muhammad Irfan Fauzan; Fiqi Ardi Abdurahman Masdar; Ahmad Ryansyah; Refansa Febriana Akbar; Alfiana (Indo Publishing, 2025)
This study analyzes the implementation of ISO 31000:2018 risk management within Spark Design, a micro and small enterprise operating in the graphic design service sector. As part of the creative industry, Spark Design encounters various risks that may disrupt its operations, including device failures, software errors, lost design files, and ineffective communication with clients. The research employs a descriptive qualitative approach using interviews with the business owner, direct observation, and document analysis to understand the risk patterns emerging in daily activities. The findings reveal that Spark Design faces 20 primary risks, with five categorized as high, such as project delays, equipment damage, unstable income, and software crashes. Using the ISO 31000 framework, the enterprise is able to identify, analyze, evaluate, and propose mitigation strategies more systematically. Recommended measures include structured project scheduling, regular device maintenance, improved data security, clearer written communication, and service diversification to stabilize income. The overall results show that applying structured risk management strengthens operational reliability, maintains design quality, and enhances Spark Design’s competitiveness in the rapidly evolving creative industry.